Change in anterior chamber depth before and after phacoemulsification in eyes with a short axial length-a quasi-experimental trial - Memon, Dania; Abid, Khadijah; Israr Qazi, Hina; Chhipa, Shaukat Ali (Journal of the Pakistan Medical Association, 2026)
Objective: To determine changes in anterior chamber depth following phacoemulsification in eyes with a short axial length. Method: The quasi-experimental study was conducted at the Department of Ophthalmology and Visual Sciences, Aga Khan University Hospital, Karachi, from May 26, 2023, to October 31, 2024, and comprised cataract patients aged 30-70 years with axial length<22mm undergoing phacoemulsification. Preoperative and postoperative anterior chamber depth measurements were recorded using an intraocular lens biometer. Postoperative assessments were done one week after the surgery. Data was analysed using R studio. Results: Of the 20 patients with mean age 54.35±11.53 years, 14(70%) were females and 6(30%) were males. The total number of eyes studied was 36. Postoperatively, the mean anterior chamber depth increased significantly (p=0.001). A moderate positive correlation was found between preoperative and postoperative anterior chamber depth (p=0.049). Axial length showed a weak, non-significant positive correlation with preoperative anterior chamber depth (r=0.20, p=0.397) and a weak negative correlation with postoperative anterior chamber depth (r=-0.36, p=0.124). Age and gender were not significantly different with respect to change in anterior chamber depth (p>0.05). No intraoperative or postoperative complications were observed. Conclusion: Phacoemulsification significantly increased anterior chamber depth in eyes with short axial lengths, confirming its anatomical and clinical benefits for cataract management. Key Words: Anterior chamber depth, Biometry, Cataract, Phacoemulsification, Short axial length.